Development of a cold stamping process for forming single-welded elbows. Issue 5 (February 2017) - Yu, Gaochao; Zhao, Jun; Wang, Chunge; Zhai, Ruixue; Ma, Rui
Abstract This paper presents a cold stamping process for single-welded elbows, which has advantages of no heating, no adjusting roundness and single weld. This process is particularly suitable for forming large diameter thin-walled deep-water pipeline elbows. The main procedure composes of blanking, machining groove, U-forming, O-forming, welding, and removing excess material. The initial blank is calculated inversely by Dynaform software, and then the finite element model of cold stamping process is developed to simulate the deformation process under different process parameters by ABAQUS software. The forming tools are designed and the experiments are carried out. Finally, the U-forming process and the O-forming process are analyzed and possible causes of the elbow wrinkling are studied. When the compression ratio is 0.75 % and the clearance between the U-punch and die is 1.05 times of blank thickness, the formed pipe elbow will be with good quality. The geometric parameters of formed elbows from FEM and the experiment are tested, the results show that the ovality is less than 0.6 %, the maximum thickening rate is less than 12 %, and the maximum thinning rate is less than 8 %. All of these verify the feasibility of the cold stamping process for forming the single-welded elbow.